Self-censorship in using social media in Bangladesh: Does regime structure matter? - Sabrina Nughat (Journal of Governance and Accountability Studies, 2024)
influences social media users' self-censorship by examining how repression, legal frameworks, surveillance, and media control affect online expression and free speech. Method: This study on self-censorship in Bangladesh used interviews, content analysis, focus groups, and surveys to understand users' online behavior under a hybrid regime. The results showed that laws such as the Digital Security Act increased self-regulation. Results: The study revealed that regime structure significantly impacts self-censorship on social media in Bangladesh. Democratic environments reduce self-censorship, whereas restrictive regimes increase it. Higher educational levels are associated with greater self-censorship, likely due to heightened awareness of the consequences. Gender and government actions had a minimal impact. An interaction effect demonstrates that a "climate of fear" combined with critical content intensifies self-censorship, emphasizing the role of regime type and freedom of expression in shaping online behavior. Limitations: The study on self-censorship in Bangladesh has limitations, including sample bias, potential inaccuracies due to self-reporting, overlooking regional variations, and cultural factors, which affect the generalizability of findings across different contexts. Contributions: This study provides valuable insights into how the regime structure influences self-censorship on social media in Bangladesh. By highlighting the correlation between authoritarian tendencies and increased self-censorship, this study elucidates the impact of laws such as the Digital Security Act on online behavior. The findings contribute to understanding the broader effects of political regimes on digital expression, offering a framework for examining self-censorship in varying political contexts, and informing future research on digital rights and freedom of expression.